Perlindungan Hukum Dan Faktor Penghambat Pengurusan Hak Cipta Batik Tulis Di Kota Kediri - Zainal Arifin; Mochammad Wachid Hasyim (Universitas Merdeka Madiun, 2019)
The works of Handmade batik in the City of Kediri are original works of the archipelago. Traditional handmade batik in the City of Kediri who are members of five groups of artisans who have been working, no one has a certificate of intellectual property rights in the form of a copyright certificate from the Ministry of Justice of the Republic of Indonesia. The research questions are: 1. How is the legal protection of handmade batik implemented in Kota Kediri? 2. What are the efforts of the City Government of Kediri in helping batik artisans to obtain batik art copyright certificates in Kediri City? 3. What are the inhibiting factors for batik copyright registration in Kediri City ?. This study uses juridical empirical methods by interviewing informants and field observations. The results are found to be several inhibiting factors why craftsmen do not have written batik copyright certificates, namely internal factors and external factors.